Implementation and Effectiveness of Religious Development Programs through Habit-Forming Strategies in Shaping Students’ Character - Abadi, Sri Bintang; Toyibah, Putri Salisatu; Alfadhillah, Khoirunnisa; Suhartini, Andewi; Martaleni, Yesi (LifeSciFi, 2025)
Religious education plays a crucial role in shaping students’ values, habits, and spiritual discipline from an early age. This study aims to describe the implementation of the religious development program for students and analyze the effectiveness of habit-forming strategies in shaping students’ religious character. The research approach uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study show that the main activities of the religious program include Duha prayers every Tuesday-Friday, daily congregational Zuhr prayers, daily donations, memorization of the Qur’an, and Night for Building Faith and Piety activities. The implementation of the program is supported by a habitual approach combined with the integration of religious values into all subjects and a character assessment system based on the observation of students’ religious behavior. The support of the school environment and parental involvement are important factors in the sustainability of the program. Analysis based on Glock and Stark’s theory shows that this program covers all dimensions of religious diversity, namely ideology, ritual, experience, intellectual, and consequential. Thus, the development of religious diversity is effective in shaping students’ religious attitudes, spiritual discipline, and social character.